Numerical Modeling of Electromagnetic Field Influences on Fluid Thermodynamic Behavior and Grain Growth During Solidification of 316L Stainless Steel Laser-Welded Plates - Zhengwei Zhang; Xinyuan Xu; Peng Ge; Kai Li (Metals, 2025)
In the present study, a thermal–electromagnetic hydrodynamics model has been used to study welding temperature and melt flow characteristics during the laser welding of 316L steel. This welding was performed using an assisted electromagnetic field. In addition, a Monte Carlo model was used to study grain growth during solidification with the purpose of achieving a better understanding of the control of the microstructure. Based on the numerical model, which has been validated by experimental data, the effects of the current intensity of the electromagnetic field on the temperature distribution, melt flow characteristics, and grain growth are discussed here in detail. The simulation results showed that both Marangoni convection and welding temperature could be controlled by the magnetic damping effect, and that they increased due to the electromagnetic heating effect when using an electromagnetic field. Furthermore, when controlling the temperature distribution and melt flow velocity in the laminar flow of the melt pool, which was assisted by a 30 A current intensity of the electromagnetic field, the temperature gradient decreased by 13.5%. This decrease could be even larger than 50% when a turbulent flow was formed in the melt pool, which has here been demonstrated for a current intensity of 100 A. In addition, undercooling was found to decrease because of the increase in the melt flow velocity when using an assistive electromagnetic field. This led to a longer nucleation time in the melt pool. Furthermore, more and larger directional columnar grains, grown by the driving force of the temperature gradient, could be formed after the consumption of the small, nucleated grains near the solid–liquid interface. In short, by controlling the temperature distribution and melt flow velocity, the required grain morphology (equiaxed or columnar) and dimension (radius, length, or width) can be controlled by coarsening and epitaxial growth.